2017
DOI: 10.1007/s00198-017-3949-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bone mineral density and microarchitectural parameters by DXA and HR-pQCT in 37 children and adults with X-linked hypophosphatemic rickets

Abstract: In XLH patients, DXA measurements must be analyzed with caution due to the interference of anatomic and anthropometric factors. HR-pQCT analysis suggested that XLH primarily affects the cancellous compartment, with the tibia more affected than the radius. Effective treatment of XLH appears to positively affect bone mineralization, mainly in the bone cortex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 17 publications
3
21
0
Order By: Relevance
“…Colares Neto and colleagues (47) in 2017 reported significantly higher lumbar spine BMD in adults, but not in children, with XLH. No significant BMD difference was found at the femoral neck, hip, or distal radius versus healthy controls . Perhaps the difference between axial and appendicular BMD Z ‐scores in adults with XLH reflects extraskeletal calcification due to enthesopathy or spinal osteophytes.…”
Section: Discussionmentioning
confidence: 91%
“…Colares Neto and colleagues (47) in 2017 reported significantly higher lumbar spine BMD in adults, but not in children, with XLH. No significant BMD difference was found at the femoral neck, hip, or distal radius versus healthy controls . Perhaps the difference between axial and appendicular BMD Z ‐scores in adults with XLH reflects extraskeletal calcification due to enthesopathy or spinal osteophytes.…”
Section: Discussionmentioning
confidence: 91%
“…In aBMD, a size artifact arises, where small bones seem to have lower BMD and large bones higher BMD. Considering the growth disturbances in XLH, DXA results have to be interpreted with caution (16). To account for this size artifact, Carter et al proposed a calculation of bone mineral apparent density (BMAD) to estimate volumetric BMD (vBMD) (7,17).…”
Section: Introductionmentioning
confidence: 99%
“…Beck-Nielsen et al reported that children and adults with XLH have elevated BMAD of the lumbar spine (7). However, Colares Neto et al examined 37 children and adults with XLH stratified by age group and reported that mean aBMD was only elevated in adults (16). DXA interpretation in XLH patients remains complex and results may not accurately portray bone mineralization (7,16).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations